Implementation of Hygiene and Sanitation in the Pastry Department of Sheraton Bali Kuta Resort Hotel - Zahra Putri Andini (Publikasi Indonesia, 2024)
This study aims to analyze the implementation of hygiene and sanitation in the pastry department of the Sheraton Bali Kuta Resort Hotel. The research method used was direct observation and interviews with several staff involved. The results showed that the standard operating procedures (SOPs) for personal hygiene had been implemented quite well, but some procedures were often forgotten due to a lack of staff awareness. In addition, SOPs for cleaning areas and equipment have also been implemented well, although there are shortcomings in maintaining consistency, such as negligence in cleaning certain areas. The high level of hotel busyness is also a factor in the cause of this negligence. Another problem found was the lack of awareness of the staff in returning the equipment to the designated place, which resulted in the loss of some equipment. In conclusion, increased awareness and staff training are needed to ensure that the implementation of hygiene and sanitation runs more consistently and effectively.